2020
DOI: 10.3390/foods9050589
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Egg White Protein and Soy Protein Isolate Addition on Nutritional Properties and In-Vitro Digestibility of Gluten-Free Pasta Based on Banana Flour

Abstract: The effects of egg white protein and soy protein isolate addition on the nutritional and digestibility of gluten-free pasta based on banana flour were studied. The level of protein additions (soy protein or egg white protein) were 0, 5, 10 and 15% of banana flour (w/w). Pasta made from 100% durum wheat semolina was used as a control. Soy protein isolate inclusion into banana pasta increased total phenolic content (TPC) and antioxidant capacities, while egg white protein decreased the TPC and antioxidant capaci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 36 publications
1
8
0
Order By: Relevance
“…On the other hand, as the protein contents of the bread samples increased, in vitro protein digestibility values were also increased ( Table 3 ). In agreement with this observation, it was found that [ 68 ] egg white protein and soy protein isolate addition improved the protein digestibility of gluten-free pasta based on banana flour.…”
Section: Resultssupporting
confidence: 70%
“…On the other hand, as the protein contents of the bread samples increased, in vitro protein digestibility values were also increased ( Table 3 ). In agreement with this observation, it was found that [ 68 ] egg white protein and soy protein isolate addition improved the protein digestibility of gluten-free pasta based on banana flour.…”
Section: Resultssupporting
confidence: 70%
“…An elemental analyser (Model Vario Max CN, Hanau, Germany) with Callidus software (EuroVector SpA, Milan, Italy) was used to determine crude protein in the samples according to the Dumas method (Rachman et al ., 2020). The crude proteins were expressed as g/100g of fresh weight.…”
Section: Methodsmentioning
confidence: 99%
“…SPI is a complex mixture of proteins, mostly globulins with numerous applications in meat analogues products [ 10 ], gluten-free foods, and cereal-based products [ 11 ]. SPI addition can improve the nutritional qualities, digestibility properties, and other characteristics of banana pasta [ 12 ] and rice dough [ 13 ]. At present, there is no report about the effect of SPI on the quality of flat rice noodles.…”
Section: Introductionmentioning
confidence: 99%